(untitled) (Journal of Civil Engineering Researchers, 2021)
An earthquake is one of the most common natural phenomena, which causes a lot of human and financial losses due to the impossibility of predicting and preventing it. Iran is one of the regions with high earthquake risk in the world due to special tectonic conditions and the existence of active faults and high seismicity. New methods in earthquake engineering, especially in recent decades, have had a significant impact on reducing seismic damage to structures. Over the years, researchers have introduced a variety of methods to reduce earthquake damage to structures. However, the existence of economic issues arising from the use of innovative equipment has always been the subject of public debate. Structural control is one of the effective methods of earthquake engineering to reduce seismic response. Structural control means that the characteristics of the dynamic behavior of the structure are adjusted in such a way that the response of the structure does not exceed the allowable limits due to external stimuli. One way to control the structural behavior is to use dampers. In this research, the performance of a multi-level pipe in pipe damper and a new brace-type slit damper in structures is investigated. In this paper, first, four structural models including two 5 and 10 story models with the same plan and two 10 and 15 story models with the same plan are modeled in SAP software. Then the same structure is examined by considering the pipe damper in the pipe. The results show that the presence of this type of damper reduces the structural responses, including drift and displacement of the maximum roof to an acceptable extent. Also, according to the models, the performance of brace-type slit damper was better than multi-level pipe in pipe damper.